Designing "Core–Shell" Insoluble‐SiW11Fe@δ‐Bi2O3 Z‐Scheme Heterojunction for Photo‐Driven Nitrogen Reduction Reaction and Evaluating the Impact of Oxygen toward Nitrogen Reduction. Issue 11 (1st March 2022) - Yang, Peng; Zhao, Ruixue; Liu, Jiquan; Wang, Tianyu; Feng, Caiting; Hu, Huaiming; Xue, Ganglin
Abstract: Photo‐driven nitrogen fixation is regarded as a promising sustainable strategy to generate low‐concentration NH3 /NH4 + . Insoluble SiW11 Fe@δ‐Bi2 O3 with "core–shell" structure and Z‐scheme featured heterojunction is constructed under solvothermal conditions. Chemisorption of nitrogen improves significantly due to increased oxygen vacancies on δ‐Bi2 O3 as induced by insoluble SiW11 Fe salt. Z‐scheme heterojunction is suggested according to energy diagram analyses and electron paramagnetic resonance spin‐trapping experiments, which can be well correlated to enhanced transient photocurrent and catalytic efficacy. [Ru(bpy)3 ] 2+ counter ion in the composite acts as a photosensitizer, leading to improved light harvesting. These merits account for superior performance of Ru2.5 SiW11 Fe@δ‐Bi2 O3 . NH3 /NH4 + production rate of 121 µmol gcat −1 h −1 is achieved under simulated sunlight irradiation in nitrogen atmosphere, but reduces on switching to air. The impact of oxygen over nitrogen reduction is investigated, and productions of both NH3 /NH4 + and H2 O2 are evaluated when using gas mixture feedstock with different V (N2 ): V (O2 ) ratios. The performance of nitrogen reduction depends mainly on its volume ratio in mixture feedstock, in addition to reduction capability of photocatalyst. By reducing the latter one appropriately, nitrogen reduction would be slightly favored when using air as feedstock. Abstract : Insoluble‐SiW11 Fe@δ‐Bi2 O3 composite with "core–shell" structure and Z‐scheme featured heterojunction is constructed. In photo‐driven nitrogen reduction, NH3 /NH4 + production rate of 121 mol gcat −1 h −1 is achieved over Ru2.5 SiW11 Fe@δ‐Bi2 O3 . The impact of oxygen over nitrogen reduction is investigated under N2 /O2 mixture atmosphere. It is found that oxygen reduction is sensitive toward the reduction capability of photocatalyst when comparing with nitrogen reduction.